2019
DOI: 10.1007/s10040-018-1901-4
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between climate change, sanitation, and groundwater quality: a case study from Ramotswa, Botswana

Abstract: Groundwater quantity and quality may be affected by climate change through intricate direct and indirect mechanisms. At the same time, population growth and rapid urbanization have made groundwater an increasingly important source of water for multiple uses around the world, including southern Africa. The present study investigates the coupled human and natural system (CHANS) linking climate, sanitation, and groundwater quality in Ramotswa, a rapidly growing peri-urban area in the semi-arid southeastern Botswa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…The conversion of natural vegetation to residential land uses increases impervious areas and hence, decreased infiltration to underlying soils and storage capacity [54], increased storm runoff, which may lead to high levels of pollution (surface and groundwater) [117] and floods, and may also cause the surface temperature to rise leading to urban heat islands [102]. This is the case of Ramotswa village within the catchment, where nitrate levels were found to be high in boreholes with samples of faecal coliform contamination, suggesting mainly a human source (i.e., from seeping pit latrines) [112]. Therefore, with increase in the population of an area, more land will be required for settlements, leaving the water sources susceptible to pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of natural vegetation to residential land uses increases impervious areas and hence, decreased infiltration to underlying soils and storage capacity [54], increased storm runoff, which may lead to high levels of pollution (surface and groundwater) [117] and floods, and may also cause the surface temperature to rise leading to urban heat islands [102]. This is the case of Ramotswa village within the catchment, where nitrate levels were found to be high in boreholes with samples of faecal coliform contamination, suggesting mainly a human source (i.e., from seeping pit latrines) [112]. Therefore, with increase in the population of an area, more land will be required for settlements, leaving the water sources susceptible to pollution.…”
Section: Discussionmentioning
confidence: 99%
“…This is because drought and water scarcity can reduce the usability of water-based sanitation and cause sewers to block (Howard et al, 2010). During periods of water scarcity in a peri-urban community in Botswana, residents with toilets connected to a sewer reverted to using old pit latrines, or built new ones, putting water supplies further at risk due to contamination (McGill et al, 2019). Other studies have found composting toilets and pit latrines are the most resilient to climate change, as they do not rely on water supply (Sherpa et al, 2014;Luh et al, 2017) or because adaptations are feasible (Howard et al, 2010).…”
Section: Climate Changementioning
confidence: 99%
“…Stress testing options under a range of plausible climate conditions relevant to the local context may assist in the management of uncertainty, and may help decision-makers to debate trade-offs between robustness, cost, safety margins, flexibility and regret (Hallegatte et al, 2019). More broadly, considering climate adaptation and mitigation also means that planning and policies need to incorporate and address the interconnections between climate, water resources, sanitation and water infrastructure, rather than consider these issues separately (McGill et al, 2019).…”
Section: Climate Changementioning
confidence: 99%
“…1a) and in the northern area around Thamaga village, where the dominant lithology is porphyritic alkali feldspar granites of the Thamaga Formation (Gaborone Granite) and the porphyritic rhyolites of the Kanye Formation; (ii) from the Nnywane Dam to the outskirt of Gaborone the geology is dominated by the sediments of the Lobatse Group and the Transvaal Supergroup; (iii) the area around Gaborone, again characterized by porphyritic alkali feldspar granites and by the porphyritic rhyolites of the Kanye Formation (for a review see Franchi and Mapeo 2019). Granites and rhyolites form low productivity, weathered/fractured aquifers while the Ramotswa dolomite (Taupone Dolomite Group) forms a productive, regionally important karstic aquifer (McGill et al 2019). The Notwane Dam (and the Gaborone Dam) rests on top of the porphyritic alkali feldspar granites of the Gaborone Granite and the Kanye Formation rhyolites (Fig.…”
Section: Study Areamentioning
confidence: 99%